Model pembelajaran soft skill terintegrasi pada siswa SMK program studi keahlian tata boga - Siti Hamidah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2012)
Kajian model pembelajaran soft skills terintegrasi bertujuan untuk mengkaji model hipotetik dari pembelajaran soft skills siswa SMK Boga. Model dikembangkan berdasarkan kajian konsep-konsep soft skills dikaitkan dengan konteks pembelajarannya pada bidang tata boga. Soft-skills diidentifikasi dari kurikulum jasa boga kelompok produktif dan dieksplorasi dari dunia industri terkait. Kemudian soft skills dari hasil identifikasi ini diintegrasikan dengan pendekatan topik dan multi target. Implementasinya dalam pembelajaran menggunakan pendekatan psikologi pemebelajaran eklektik antara behaviourisme, kognitvisme, konstruktivisme, dan humanisme. Rancangan model ini menekankan peran aktif siswa mulai dari merancang perilaku soft skills, mengkonstruk soft skills terintegrasi melalui pengalaman belajar berbasis manajemen kinerja, dan melakukan refleksi untuk perbaikan berkelanjutan. SOFT-SKILLS INTEGRATED LEARNING MODEL FOR VOCATIONAL HIGH SCHOOL STUDENTS OF HOME ECONOMICS EDUCATIONAbstractThis study of soft-skills integrated learning model was aimed at investigating a hypothetic model of learning for Vocational High School students of home economics education. The model was developed from concepts of soft-skills as well as the learning within the context of home economics education. The soft-skills were identified through out of the curriculum of vocation for food service program as well as through out demanded soft skills by industries partners. The identied soft skills then, integrated into the curriculum by using topics and muli-target approaches. This model is implemented by eclecitally combining among these four psychological approaches. This model design indeed encouraging students actively ranging from pre-determined soft skills to be achieved, constructing integrated soft skills through learning experience based on performance management, and reflecting for a sustainable improvement of student soft skills.